Pengembangan Sistem Pembayaran Berbasis Blockchain dalam Perbankan Syariah: Peluang, Tantangan, dan Perspektif Regulasi - Harahap, Khairunnisa; Hendrawan, Yoni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The digital transformation in the Islamic financial sector requires the development of more efficient, secure, and transparent payment systems. This study aims to explore the opportunities and challenges of blockchain-based Islamic payment systems and proposes a conceptual framework for developing secure and sharia-compliant digital payment systems. Using a conceptual literature review method and qualitative content analysis of academic sources and regulatory documents, this study finds that blockchain can enhance the efficiency and transparency of Islamic payment systems but requires dual auditing (shariah and technical) and adaptive regulations. This article introduces the “Sharia-Compliant Blockchain Payment Framework”, an original model that integrates Islamic principles from the design stage of digital payment systems. This study represents one of the first conceptual efforts to propose a sharia-compliant blockchain-based payment system framework, contributing to the advancement of Islamic economic law in the digital era.